Design of a recyclable Y2O3-g-C3N4 as an auspicious nanosorbent for removing malachite green dye - Zainab M.H. El-Qahtani; A. Modwi; Hanadi M. AbdelSalam; Tahani M. Albogami; I.A. Osman; Eida S. Al-Farraj; Azizah A. Algreiby (Journal of Science: Advanced Materials and Devices)
The recent development of industrial and agricultural technology has led to severe environmental damage, most notably water pollution, which poses a serious threat to water security, considering population increases and a decrease in global drinking water sources. In this direction, a nanostructure (Y2O3-g-C3N4) with a BET surface area of 82.14 m2. g−1 was employed for the first time as a novel sorbent to remove malachite green (MG) from the aqueous phase. Besides, the SEM, TEM, and EDX data verified the integration of 14.17 nm Y2O3 nanoparticles into the g-C3N4 nanosheets. The experimental adsorption results confirmed the best fitting to the well-known Langmuir isotherm equation, achieving qmax = 1297 mg g1 of MG uptake, and the kinetic model calculations revealed a single-step mechanism involving a pseudo-second-order chemical reaction with a rate constant of 0.00134 mg./mg. min, which accounted for the chemisorption of MG dye on the Y2O3-g-C3N4 nanostructure sample. Due to its ease of manufacture and ecologically acceptable procedure, the Y2O3-g-C3N4 nanostructure was recognized as a desirable and promising candidate for eradicating tainted organic dyes. The newly synthesized Y2O3-g-C3N4 nanostructure with a high surface area demonstrated a short contact time, outstanding removal capacity, five times recyclability, and multiple dyes elimination nominating it a potentially valuable nanosorbent for the adsorption of dyes from wastewater.